DEPLOYMENT OF HONEYPOTS AS PROACTIVE DETECTION TOOLS FOR MONITORING CYBER RELATED INCIDENCES - Ogada, Peter Odhiambo; Raburu, George; Liyala, S.; Okelo, N. B (IJRDO -Journal of Computer Science Engineering, 2015)
The Kenya government is striving to roll out its Vision 2030 programme where ICT plays amajor role in achieving the components of the Pillars associated with it. The purpose of thisstudy was to find out the extent to which deployment of HoneyPots as early warning detectiontools for monitoring cyber related incidents had been embraced within KENET memberinstitutions in Western Kenya, how they are aiding the institutions in knowing and understandingtheir adversaries; and allowing them to implement solutions that work in defending the criticalinternet and network infrastructures they manage. The study was guided by a descriptive studydesign with a study population of 117 staff members working in various institutions in westernKenya. Using simple random sampling technique, a sample size of 80 respondents were pickedand administered with questionnaires, 70 questionnaires were returned for data entry andanalysis using Statistical Package for social Sciences version 20. This implies that 87.5% of therespondents turned up for the study. According to the major findings, the study established thatmost of the KENET member institutions in western Kenyan, despite experiencing cyber securityrelated incidents, had not setup CIRT teams nor deployed Honeypots to help them study cybersecurity incidents and take appropriate action to defend their constituencies. As arecommendation, the Government, being one of the economic stakeholders, and KENET, shouldcome up with intervention measures through the Ministry of ICT making it mandatory for setupCIRTs. All CIRTs should then be required to direct part of their traffic to the national CERTwhich ideally should be based at Communication Authority of Kenya to form a Honey Net,which can further be linked with other internationally recognized Honey Net projects